Familienleitbilder in Deutschland Kulturelle Vorstellungen zu Partnerschaft, Elternschaft und Familienleben - Schneider, Norbert F.; Diabaté, Sabine; Ruckdeschel, Kerstin (Beitrage zur Bevölkerungswissenschaft, 2015)
Which cultural concepts of family life exist in Germany? What is considered "normal", "desirable", and "deviant" and how do these ideas influence family formation and family life? These questions are the focus of the contributions collected in this volume, in which the diversity and contradictoriness of family models in Germany are identified. This book thus makes an important contribution to explaining the cultural understanding of demographic processes. Recommendations for future research and family policy are derived from the results of the study in order to better meet the needs of young people in Germany.